KADAR LOGAM BERAT MERKURI (Hg) PADA KERANG HIJAU DI PURWOKERTO KABUPATEN BANYUMAS TAHUN 2018 - Riska Auliyah; Tri Marthy Mulyasari; Bayu Chondro Purnomo (Poltekkes Kemenkes Semarang, 2019)
Along with the increasing of industry in indonesia and the use of various heavy metal materials can have a negative impact one of it is the water pollution by mercury (Hg) heavy metal. Sea water pollution has a very serious impact for the humans, especially who consume sea biota that is come from contaminated waters region. Sea biota that can be used as an indicator of heavy metal pollution is the shellfish. The purpose of this research is to determine the amount of heavy metal mercury (Hg) in the green shells that is sold in Purwokerto Banyumas Regency. The kind of this research is descriptive research. Green shells (pema viriois) samples that are inspected 3 samples. The respondent of this research are green shell seller at Puwokerto Banyumas regency as much as 3 respondents. The Inspection of mercury heavy metal content on green shell using SSA method at The Great Hall of Industry Pollution Prevention Technology (BBTPPI ) Semarang. The Result of merkury (Hg) heavy metals measurement from the green shellfish sample at DK seller 0,022 mg / kg, DKR seller 0,022 mg / kg, and SHS seller 0,021 mg / kg The green shell of DK sample is taken from Alam Indah Beach at Tegal, DKR sample is taken from Kartini sea at Jepara, and SHS sample is taken from Widuri sea Pemalang. The result of respondent knowledge about the danger of mercury (Hg) on the green shell is 28% of Mr A sample respondents, 24% of Mr B respondents and 42% of Mrs C respondents. The researcher concluded that the amount of mercury (Hg) heavy metal on 3 samples of green shell has fulfilled the requirements of the Obal and Food Supervisory Agency of the Indonesian Republic No.HK.00.05.1.52.4011 Year 2009 about the deermination of the maximum contamination limit of microbial and chemical in thr food that is 1.0 Ppm or mg / kg